Bildungsgangarbeit in beruflichen Schulen – Praxisphasen und ihre Auswirkungen in der Bildungsgangarbeit - Beutner, Marc (Wirtschaftspädagogische Handlungsfelder. Festschrift für Peter F. E. Sloane zum 60. Geburtstag)

Kamm, J. / Lenz, B. (Hg.): Representing Terrorism and Deconstructing Terrorism - Tönnies, Merle (Arbeiten aus Anglistik und Amerikanistik)

E-Learning zur Sprach- und Berufsförderung – Einblicke in AGnovel. Advanced Graphic novels in der Beruflichen Bildung - Beutner, Marc; Fortmann, M; Pechuel, R (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Entrepreneurship und Berufliche Bildung: UMW – Under my Wing – Ein Innovationsprojekt zur Unterstützung von Absolventen aus nicht geschäftsbezogenen Disziplinen bei der Unternehmensgründung - Beutner, Marc; Fortmann, L. M. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Wiki-Wonderland? – Eine Qualitative Analyse zu Vor- und Nachteilen von Wikis für Lehrende und Studierende - Flotmann, Christina (Lehr- und Lernpraxis im Fokus – Forschungs- und Reflexionsbeiträge aus der Universität Paderborn)

Political Rhetoric as a Structural and Ideological Instrument in Star Wars and Harry Potter - Flotmann, Christina (Politics in Fantasy Media: Essays on Ideology and Gender in Fiction, Film, Television and Games)

Medienbildung mit Informatik-Anteilen!? - Klar, Tilman-Mathies; Engbring, Dieter (Gestalten und Meistern von Übergängen. 6. Tagung Hochschuldidatik der Informatik)

Improving the bond quality of copper wire bonds using a friction model approach - Althoff, Simon; Neuhaus, Jan; Hemsel, Tobias; Sextro, Walter (Electronic Components and Technology Conference (ECTC), 2014 IEEE 64th)
In order to increase mechanical strength, heat dissipation and ampacity and to decrease failure through fatigue fracture, wedge copper wire bonding is being introduced as a standard interconnection method for mass production. To achieve the same process stability when using copper wire instead of aluminum wire a profound understanding of the bonding process is needed. Due to the higher hardness of copper compared to aluminum wire it is more difficult to approach the surfaces of wire and substrate to a level where van der Waals forces are able to arise between atoms. Also, enough friction energy referred to the total contact area has to be generated to activate the surfaces. Therefore, a friction model is used to simulate the joining process. This model calculates the resulting energy of partial areas in the contact surface and provides information about the adhesion process of each area. The focus here is on the arising of micro joints in the contact area depending on the location in the contact and time. To validate the model, different touchdown forces are used to vary the initial contact areas of wire and substrate. Additionally, a piezoelectric tri-axial force sensor is built up to identify the known phases of pre-deforming, cleaning, adhering and diffusing for the real bonding process to map with the model. Test substrates as DBC and copper plate are used to show the different formations of a wedge bond connection due to hardness and reaction propensity. The experiments were done by using 500 $μ$m copper wire and a standard V-groove tool.
Keywords: adhesion; circuit reliability; deformation; diffusion; fatigue cracks; friction; interconnections; lead bonding; van der Waals forces; Cu; adhering process; adhesion process; ampacity improvement; bond quality improvement; cleaning process; diffusing process; fatigue fracture failure; friction energy; friction model; heat dissipation; mechanical strength; piezoelectric triaxial force sensor; predeforming process; size 500 mum; total contact area; van der Waals forces; wedge copper wire bonding; Bonding; Copper; Finite element analysis; Force; Friction; Substrates; Wires

Self-Sensing Ultrasound Transducer for Cavitation Detection - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Memoli, Gianluca; Hodnett, Mark; Zeqiri, Bajram (2014 IEEE International Ultrasonics Symposium Proceedings)
Cavitation monitoring is desired to optimize the sonication for diverse sonochemical processes and to detect changes or malfunctions during operation. In situ cavitation measurements can be carried out by detection of the acoustic emissions of cavitation bubbles by sensors in the liquid. However, in harsh environments sensors might not be applicable. Thus, the impact of cavitation on the electrical signals of a piezoelectric transducer has been analyzed as alternative method to measure the threshold, strength and type of cavitation. The applicability has been tested in three different setups to evaluate the general- izability of extracted indicators. In all setups indicators for the cavitation thresholds could be derived from the current signal. In two setups features showed two thresholds that may be linked to the types of cavitation. However, only one feature derived from the current signal in one particular setup correlated to the strength of cavitation. Cavitation detection based on the current signal of the transducer is a useful method to detect cavitation in harsh environments and without perturbing the sound field. Once appli- cable indicators have been identified, they may easily be tracked during the process. However, for more detailed studies about the cavitation activity and its spatial distribution, measurements with in situ sensors are recommended.

Microstructural investigations of aluminum and copper wire bonds - Eacock , Florian; Schaper, Mirko; Althoff, Simon; Unger, Andreas; Eichwald, Paul; Hengsbach, Florian; Zinn, Carolin; Holzweissig, Martin Joachim; Guth, Karsten (Proceedings of the 47th International Symposium on Microelectronics)
Nowadays wire bonding is a widely-used technology for interconnecting chips in the packaging industry. Thereby, it is known that the bond quality massively depends upon the microstructure prevailing in the bond and consequently the materials used as well as the bonding parameters. However the actually used materials such as aluminum and gold are either characterized by comparibly poor conductivity or high costs, respectively. Due to its outstanding properties copper is a more attractive candidate. Still, a thorough investigation on the interrelationship between the material combinations, the processing parameters and the resulting microstructure for copper and aluminum wire bonding was not carried out yet. Depending on the aforementioned factors the microstructural evolution can be completely different during the bonding process. Therefore, this study focuses on the microstructural evolution of heavy copper and heavy aluminum wires bonded on copper substrates. The evolution of the wire microstructure as well as the wire-substrate-interface was investigated by scanning electron microscope in combination with electron backscatter diffraction and microhardness measurements. Various samples were extracted at different points of the bonding process, namely the as-received condition, after touchdown and after completed bonding. The results of the aluminum and copper wires were compared to each other in both longitudinal and transversal direction. It was found, that the two wire materials were completely different in the as-received condition regarding the grain size, the grain morphology, the texture and the microhardness. After touchdown the microstructure did not show significant changes in both materials, yet a strain-hardening was observed in the copper wire resulting from the touchdown force. When the bonding process was completed a different microstructure could be observed in both the wire as well as the layer for the materials investigated. Furthermore, a destinctive increase in the wire hardness could be found in case of copper, which was not observed for the aluminum wire. The ramifications between the two wire materials presented in this work will be discussed with the objective of optimizing the quality of the bonds.
Keywords: Bonding; Copper; Microstructure evolution

Analysis Method of Tool Topography Change and Identification of Wear Indicators for Heavy Copper Wire Wedge Bonding - Eichwald, Paul; Sextro, Walter; Althof, Simon; Eacock, Florian; Unger, Andreas; Meyer, Tobias; Guth, Karsten (Proceedings of the 47th International Symposium on Microelectronics)
Wire bonding is the most common technology for connecting electronic components. Due to their efficiency bond interconnections made of copper wire are used for example in the aerospace and medical technology as well as in the fields of renewable energies. One of the main cost factors in the manufacturing process is the consumables like bonding tools. The technological transition to copper as wire material causes significant wear on the millimeter large effective contact area of the bonding tool. This wear leads to a loss by a factor of 30 of the number of reliable interconnections which can be produced by a single tool. To reduce setting-up time in the production and minimizing costs, an enlarged bonding tool lifetime is desirable. Consequently a better understanding of wear and recognition of wear pattern is required. Therefore, the paper presents an analyzing method of the tool topography change of a heavy wire bonding tool by using a confocal microscope. Furthermore, the paper discusses the identification of the main wear indicators by the help of the named topography change for different bond parameters, like ultrasonic power and tool geometry. Reference topography has been carried out by choosing typical parameters of the production line. To judge whether the quality requirement of the bond connections made by a single tool cannot be fulfilled shear test of the source bond have been carried out after a defined number of produced bond connections. Main steps of analysis: (I)Topography of the tool surface is sampled after a defined number of bonds by means of a confocal microscope to detect the wear progress.(II)The recorded data is filtered using Matlab. So, measurement errors can be eliminated and the topography can be overlaid more easy to identify differences between diverse tools or differences in wear stages of the same tool.(III)The subsequent discretization of the topography into sub volumes allows to (IV)describe the loss of volume depending on the position in the groove. Thereby, intermediate status of wear of one tool can be used to obtain a persistent description of the topography change over the number of produced bonds by interpolating the confocal data. Afterwards the persistent change of the groove flank has been analyzed for the named test series to identify the main wear indicators and their effect on shear forces. All worn tools show dominant areas for volume loss especially for plastic deformation and accordingly abrasion. These wear mechanism can be referred to the change of main parts of the groove geometry like the rounding of the front and back radius. The most volume loss was identified in the upper part of the tool flanks or rather at the transition from the groove flank to the front or back radius. Furthermore the observation of the center of the groove flank shows just a little change in volume. All in all, the identification of the wear indicators will be discussed with the objective of increasing the tool lifetime by optimizing the tool geometry without losses in bond quality and reliability.
Keywords: wedge/wedge bonding; copper wire; tool wear

Dependability of Self-Optimizing Mechatronic Systems - Gausemeier, Jürgen; Josef Rammig, Franz; Schäfer, Wilhelm; Sextro, Walter
Intelligent technical systems, which combine mechanical, electrical and software engineering with methods from control engineering and advanced mathematics, go far beyond the state of the art in mechatronics and open up fascinating perspectives. Among these systems are so-called self-optimizing systems, which are able to adapt their behavior autonomously and flexibly to changing operating conditions. The Collaborative Research Center 614 "Self-optimizing concepts and structures in mechanical engineering" pursued the long-term aim to enable others to develop dependable self-optimizing systems. Assuring their dependability poses new challenges. However, self-optimization also offers the possibility to adapt the system's behavior to improve dependability during operation. The aim of this book is to provide methods and techniques to master the challenges and to exploit the possibilities given by self-optimization. The reader will be able to develop self-optimizing systems that fulfill and surpass today’s dependability requirements easily. This book is directed to researchers and practitioners alike. It gives a brief introduction to the holistic development approach for self-optimizing mechatronic systems and the steps required to assure a dependable product design starting with the very early conceptual design phase. A guideline to select suitable methods for each step and the methods themselves are included. Each method is individually introduced, many examples and full references are given.

Reliability analysis of ultrasonic power transducers - Hemsel, Tobias; Bornmann, Peter; Morita, Takeshi; Sondermann-Wölke, Christoph; Sextro, Walter (Archive of Applied Mechanics)
Keywords: Reliability; Ultrasonic power transducers; FMEA

High-velocity operation of piezoelectric inertia motors: experimental validation - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Archive of Applied Mechanics)
Piezoelectric inertia motors use the inertia of a body to drive it by means of a friction contact in a series of small steps. It has been shown previously in theoretical investigations that higher velocities and smoother movements can be obtained if these steps do not contain phases of stiction (''stick-slip`` operation), but use sliding friction only (''slip-slip`` operation). One very promising driving option for such motors is the superposition of multiple sinusoidal signals or harmonics. In this contribution, the theoretical results are validated experimentally. In this context, a quick and reliable identification process for parameters describing the friction contact is proposed. Additionally, the force generation potential of inertia motors is investigated theoretically and experimentally. The experimental results confirm the theoretical result that for a given maximum frequency, a signal with a high fundamental frequency and consisting of two superposed sine waves leads to the highest velocity and the smoothest motion, while the maximum motor force is obtained with signals containing more harmonics. These results are of fundamental importance for the further development of high-velocity piezoelectric inertia motors.
Keywords: Inertia motor; High velocity; Stick-slip motor; Slip-slip operation; Friction parameter identification

Synthesis of lead-free piezoelectric powders by ultrasonic-assisted hydrothermal method and properties of sintered (K0.48Na0.52)NBO3 ceramics - Isobe, G.; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics, Ferroelectrics, and Frequency Control, IEEE Transactions on)
(K,Na)NbO3 ceramics have attracted much attention as lead-free piezoelectric materials with high piezoelectric properties. High-quality (K,Na)NbO3 ceramics can be sintered using KNbO3 and NaNbO3 powders synthesized by a hydrothermal method. In this study, to enhance the quality factor of the ceramics, high-power ultrasonic irradiation was employed during the hydrothermal method, which led to a reduction in the particle size of the resultant powders.
Keywords: Q-factor; ceramics; crystal growth from solution; particle size; piezoelectric materials; potassium compounds; powders; sintering; sodium compounds; ultrasonic effects; (K0.48Na0.52)NbO3; KNbO3 powders; NaNbO3 powders; high-power ultrasonic irradiation; lead-free piezoelectric materials; lead-free piezoelectric powders; particle size reduction; piezoelectric properties; quality factor; sintered (K0.48Na0.52)NbO3 ceramics; sintering; ultrasonic-assisted hydrothermal method; Acoustics; Ceramics; Lead; Piezoelectric materials; Powders; Radiation effects; Transducers

PEM fuel cell prognostics using particle filter with model parameter adaptation - Kimotho, James Kuria; Meyer, Tobias; Sextro, Walter (Prognostics and Health Management (PHM), 2014 IEEE Conference on)
Application of prognostics and health management (PHM) in the field of Proton Exchange Membrane (PEM) fuel cells is emerging as an important tool in increasing the reliability and availability of these systems. Though a lot of work is currently being conducted to develop PHM systems for fuel cells, various challenges have been encountered including the self-healing effect after characterization as well as accelerated degradation due to dynamic loading, all which make RUL predictions a difficult task. In this study, a prognostic approach based on adaptive particle filter algorithm is proposed. The novelty of the proposed method lies in the introduction of a self-healing factor after each characterization and the adaption of the degradation model parameters to fit to the changing degradation trend. An ensemble of five different state models based on weighted mean is then developed. The results show that the method is effective in estimating the remaining useful life of PEM fuel cells, with majority of the predictions falling within 5% error. The method was employed in the IEEE 2014 PHM Data Challenge and led to our team emerging the winner of the RUL category of the challenge.
Keywords: ageing; particle filtering (numerical methods); proton exchange membrane fuel cells; remaining life assessment; PEM fuel cell prognostics; PHM; RUL predictions; accelerated degradation; adaptive particle filter algorithm; dynamic loading; model parameter adaptation; prognostics and health management; proton exchange membrane fuel cells; remaining useful life estimation; self-healing effect; Adaptation models; Data models; Degradation; Estimation; Fuel cells; Mathematical model; Prognostics and health management

An approach for feature extraction and selection from non-trending data for machinery prognosis - Kimotho, James Kuria; Sextro, Walter (Proceedings of the Second European Conference of the Prognostics and Health Management Society 2014)
With the paradigm shift towards prognostic and health management (PHM) of machinery, there is need for reliable PHM methodologies with narrow error bounds to allow maintenance engineers take decisive maintenance actions based on the prognostic results. Prognostics is mainly concerned with the estimation of the remaining useful life (RUL) or time to failure (TTF). The accuracy of PHM methods is usually a function of the features extracted from the raw data obtained from sensors. In cases where the extracted features do not display clear degradation trends, for instance highly loaded bearings, the accuracy of the state of the art PHM methods is significantly affected. The data which lacks clear degradation trend is referred to as non-trending data. This study presents a method for extracting degradation trends from non-trending condition monitoring data for RUL estimation. The raw signals are first filtered using a discrete wavelet transform (DWT) denoising filter to remove noise from the acquired signals. Time domain, frequency domain and time-frequency domain features are then extracted from the filtered signals. An autoregressive model is then applied to the extracted features to identify the degradation trends. Features representing the maximum health information are then selected based on a performance evaluation criteria using extreme learning machine (ELM) algorithm. The selected features can then be used as inputs in a prognostic algorithm. The feasibility of the method is demonstrated using experimental bearing vibration data. The performance of the method is evaluated on the accuracy of RUL estimation and the results show that the method can be used to accurately estimate RUL with a maximum error of 10%.
Keywords: autoregressive model ELM feature extraction feature selection non-trending Remaining useful Life

Optimal Parameter Tuning for Multiclass Support Vector Machines in Machinery Health State Estimation - Kimotho, James Kuria; Sextro, Walter (PAMM)
The increasing demand for high reliability, safety and availability of technical systems calls for innovative maintenance strategies. The use of prognostic health management (PHM) approach where maintenance action is taken based on current and future health state of a component or system is rapidly gaining popularity in the maintenance industry. Multiclass support vector machines (MC-SVM) has been identified as a promising algorithm in PHM applications due to its high classification accuracy. However, it requires parameter tuning for each application, with the objective of minimizing the classification error. This is a single objective optimization problem which requires the use of optimization algorithms that are capable of exhaustively searching for the global optimum parameters. This work proposes the use of hybrid differential evolution (DE) and particle swarm optimization (PSO) in optimally tuning the MC-SVM parameters. DE identifies the search limit of the parameters while PSO finds the global optimum within the search limit. The feasibility of the approach is verified using bearing run-to-failure data and the results show that the proposed method significantly increases health state classification accuracy.

Tire footprint analysis depending on the elastokinematics of a multi-link suspension system using multi-body dynamics simulation - Kohl, Sergej; Sextro, Walter; Zuber, Armin (PAMM)
An automotive suspension system represents one of the most complex and important systems in a passenger vehicle, which has to ensure a robust and optimized contact between the wheels and the road at any time. For improving a suspension system it is important to take an investigative look at the interaction between suspension, tire and road dynamics. Thus a part of a study into aspects of suspension modeling on multi-body simulations of rear multi-link suspension system dynamics with focus on the tire footprint area is presented in this work.

Conclusion and Outlook - Meyer, Tobias; Priesterjahn, Claudia; Sextro, Walter (Dependability of Self-Optimizing Mechatronic Systems)